EFFECTIVENESS OF WATER HYACINTH (EICHHORNIA CRASSIPES (MART.) SOLMS.) DAN KIAMBANG (SALVINIA MOLESTA D. S. MITCHELL) IN PHYTOREMEDIATION OF MANGANESE (MN) HEAVY METAL LEVELS IN DUG WELL WATER IN SUNGAI ULIN HOUSING ESTATE, NORTH BANJARBARU DISTRICT, SOUTH - Dharmaji, Deddy; Rahman, Mijani; Saidah, Saidah (Fish Scientiae, 2025)
Dug wells are water that comes from the ground and are still widely used by Indonesians, especially in the Banjarabaru area of Sungai Ulin Housing in South Kalimantan Province. The heavy metal problem that is often encountered is manganese content. Manganese is a heavy metal that is often found in the earth's skin and is often found together with iron. Manganese heavy metal levels that exceed quality standards can make well water yellowish in color, smell of rust due to its high content and if left for several days there will be sediment in the bucket, causing a yellowish color on white clothes and can cause health problems. Improving water quality is very important, one of which is the phytoremediation method. Phytoremediation is a method of utilizing plants to remove harmful organic and inorganic substances. In this study, the authors used water hyacinth and kiambang because of their ability to absorb heavy metals in water. The purpose of this study was to determine the effectiveness of heavy metal manganese absorption using water hyacinth and kiambang plants in dug well water in Sungai Ulin Housing. The research was conducted using an experimental method using a Completely Randomized Design (CRD) with three repetitions, namely on the 3rd, 6th, and 9th days and three treatments, namely control (without the addition of water plants), water hyacinth plants and Kiambang which were carried out for 3 weeks of research. The measurement results obtained were water hyacinth plants were able to reduce manganese heavy metal levels to 0.016 mg/l with a biomass of 300 grams / 10 liters on day 9 and Kiambang water plants were able to reduce manganese heavy metal levels to 0.017 mg/l with a biomass of 500 grams / 10 liters on day 9.